Measurement of mitral regurgitation by Doppler echocardiography. Issue 4 (October 1985) - Zhang, Y; Ihlen, H; Myhre, E; Levorstad, K; Nitter-Hauge, S
Abstract : In an attempt to develop a new approach to the non-invasive measurement of mitral regurgitation, Doppler echocardiography and left ventriculography were performed in 20 patients without valvar heart disease (group A) and in 30 patients with pure mitral regurgitation (group B). Volumetric flows through the aortic and the mitral orifices were determined by Doppler echocardiography. Aortic flow (AF) was calculated as the product of the aortic orifice area and the systolic velocity integral. The mitral flow (MF) was calculated as the product of the corrected mitral orifice area and the diastolic velocity integral. The mitral regurgitant fraction (RF) was calculated as RF = 1 - AF/MF. In group A aortic and mitral flow were very similar and the difference between the two did not differ significantly from zero. In group B the mitral flow was significantly larger than the aortic flow. There was a good correlation (r = 0.82) between the regurgitant fraction determined by Doppler echocardiography and the regurgitant grades determined by left ventriculography. The regurgitant fraction increased significantly with each grade of severity. These results show that Doppler echocardiography can be used to give a reliable measure of both aortic and mitral flow. This technique is a new and promising approach to the non-invasive measurement of mitral regurgitation.